The Development of Comparative Linguistics in the Post-Independence Period of Uzbekistan - Mahkamova Shahlo (International Journal on Integrated Education, 2022)
The article describes issues related to studying the development of comparative linguistics in the post-independence period of Uzbekistan. As well as, we studied the essence of comparative linguistics and its significance in developing linguistics. Comparison of languages has theoretical and practical value. It deepens the study of each of the compared languages, contributes to the discovery of properties that remain out of sight in a separate (non-comparative) study. The results of such studies can serve as material for typology, for compiling dictionaries, as well as for the theory and practice of translation.